STUDY THE EFFICACY OF KHADIRADI KWATH IN THE MANAGEMENT OF BHAGANDARA W.S.R. TO FISTULA IN ANO - Anantkumar, Shekokar; Kanchan, Borkar; Bharat, *Kulthe (International Journal of Ayurveda and Pharma Research, 2018)
From the origin of civilization the people suffered from various diseases and among the many uncomfortable conditions, Guda Roga is one of the most important one. The disease is widely prevalent and numerous options are being practiced for its management.Fistula in ano is one condition for which the maximum types of surgical, parasurgical and medical applications have been described. This divergent approach to the treatment for a single disease is only suggestive of the fact that none of these methods is complete or satisfactory. Sushruta described a detailed surgical approach involving excision of the fistulous tract but also felt the necessity of a parasurgical approach since he was not quite satisfied with the surgical excision which often resulted into recurrence. However, they limited this alternative method called Ksharasutra in selected cases only in which found unfit for surgery. Due to Ksharsutra procedure Recurrence rate is almost nil but it takes very long duration to cut and heal the track. Khadiradi Kwaths helps to inhibit to break pathogenesis of Bhagandara in short time and also prevent the recurrence rate of Bhagandara and hence recurrence rate is nearly nill and it does not take very long duration to cut and heal the track of Bhagandara with minimum expenditure.In our present study we have taken 60 patients, in two groups, 30 patients in each group. The first group is experimental group i.e., Khadiradi Kwath along with standard Ksharsutra and second is control group i.e. only Ksharsutra. We have taken observations viz. age, sex, occupation, Agni, Koshtha etc. by which we can observe the characteristics of disease in these conditions. To assess the nature of disease we have taken assessment criteria like pain, discharge, in duration, foul smell, burning sensation, itching. From above criteria we made the result of effectiveness of treatment by using ‘t’ test on 0.001% level of significance.